Reclaiming Territory Through Conservation Areas: Gwaii Haanas, Haida Gwaii, 1851-1993 - Ingram, Gordon Brent (UnderCurrents: Journal of Critical Environmental Studies, 1995)
In 1994, after 135 years of overtures from the Haida of the north coast of Pacific Canada, the Government of British Columbia finally began negotiations with the Council of Haida Nation (CHN) for a comprehensive treaty. [...]